Social dynamics of voluntary health workers in primary health care. - Perera, M.A.L.R (My University, 1985)
A study was undertaken to: Identify predominant characteristics and activities of a group of voluntary health workers,Study the impact of activities of a primary health care development project.The following recommendations flow out of the experience gained from the study: Induced,indirect community participation in primary health care is feasible. A village health development committee and a nerwork of voluntary health workers is a suitable organization for the above purpose.The committee is to consist of village leaders.The leaders will nominate voluntary health workers.This model can be adopted on a national basis.Training of new voluntary health wokers should be an on-going activity of a primary health care development programme.The activity is designed to cater to drop- outs of vountary health workers.Such training programmes need to be arranged once in about six months.New voluntary health workers of a number of public health midwife areas could be trained together,at a central location.On the job-training of voluntary health workers needs strengthening.Evaluation of primary health care programmes should be built into such programmes.The evaluation should focus on expected changes in health practices.It is desirable for each health unit to train an evaluation team.The middle level supervisors are suitable for the purpose.Surveys of random samples of households should generate data for evaluations of primary health care programmes.The ideal characteristics of voluntary health workers.The exact contribution of voluntary health workers to any changes in the health situation in an area has to be determined.The cost benefit of the voluntary health worker programme can be thus determined.